2014
DOI: 10.1016/j.ypmed.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a primary care practice intervention for increasing colorectal cancer screening in Appalachian Kentucky

Abstract: Objective This report describes findings from a randomized controlled trial of an intervention to increase colorectal cancer (CRC) screening in primary care practices in Appalachian Kentucky. Methods Sixty-six primary care practices were randomized to early or delayed intervention groups. The intervention was provided at practices using academic detailing, a method of education where providers receive information on a specific topic through personal contact. Data were collected in cross-sectional surveys of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
(28 reference statements)
0
24
0
Order By: Relevance
“…Colon and rectum cancers are higher in Appalachia for both men and women, regardless of region, except for women in the Southern region where rates are consistent with non-Appalachia. Various studies have found lower colorectal cancer screening rates in Appalachia areas, or among persons residing in rural areas (12,30,31). Cervical cancers are also higher in Appalachia overall and appear to be driven by increased rates primarily in Central Appalachia.…”
Section: Discussionmentioning
confidence: 99%
“…Colon and rectum cancers are higher in Appalachia for both men and women, regardless of region, except for women in the Southern region where rates are consistent with non-Appalachia. Various studies have found lower colorectal cancer screening rates in Appalachia areas, or among persons residing in rural areas (12,30,31). Cervical cancers are also higher in Appalachia overall and appear to be driven by increased rates primarily in Central Appalachia.…”
Section: Discussionmentioning
confidence: 99%
“…53 These data were used to successfully advocate for a public policy requiring all health insurance companies operating in Kentucky to make screening colonoscopy a covered service for age-eligible individuals. [55][56][57][58][59] After this intensive effort, the proportion of the age-eligible population in Kentucky undergoing either colonoscopy or sigmoidoscopy rose from approximately one-third (34.7%) in 1999 to nearly two-thirds (63.7%) in 2008, and Kentucky rose from 49th in CRC screening to 23rd. These interventions included using lay health navigators to reduce cultural barriers and using academic detailing to persuade primary care providers to recommend screening to their age-eligible patients and then schedule CRC screening appointments for these patients.…”
Section: Using the Population-based Cancer Registry To Guide The Implmentioning
confidence: 99%
“…These interventions included using lay health navigators to reduce cultural barriers and using academic detailing to persuade primary care providers to recommend screening to their age-eligible patients and then schedule CRC screening appointments for these patients. [55][56][57][58][59] After this intensive effort, the proportion of the age-eligible population in Kentucky undergoing either colonoscopy or sigmoidoscopy rose from approximately one-third (34.7%) in 1999 to nearly two-thirds (63.7%) in 2008, and Kentucky rose from 49th in CRC screening to 23rd. 53 The CRC screening rates in Kentucky have continued to increase.…”
Section: Using the Population-based Cancer Registry To Guide The Implmentioning
confidence: 99%
“…Although screening tests for CRC (e.g., colonoscopy, sigmoidoscopy, stool tests) that can reduce both incidence and mortality from CRC have been available, CRC screening prevalence is lower in Appalachian regions of Kentucky and Ohio as compared to non-Appalachian regions (8). Low CRC screening rates in Appalachia are associated with intrapersonal and health care provider-related factors, but are also linked to state and community factors such as access to health care and poverty (9)(10)(11). Factors such as high poverty rates, cultural and religious considerations, and isolating geographical characteristics (12) in rural Appalachia make safety net clinics, health care providers, and community resources critical sources of preventive care.…”
Section: Introductionmentioning
confidence: 99%
“…At the clinic level, barriers to receipt of screening include lack of comprehensive educational materials and insu cient tracking systems to remind clinic staff to follow up with patients in need of screening (18). Furthermore, Appalachians have frequently encountered barriers such as lack of physician recommendation as a reason for having never received CRC screening (19), and medical professionals identi ed limited time and high patient volume as barriers to providing CRC screening, along with acute medical concerns and procedural/reimbursement issues (10,15,19). Lastly, low rates of educational attainment combined with fatalistic beliefs and fear of cancer may contribute to the lack of discussion surrounding CRC and screening (21).…”
Section: Introductionmentioning
confidence: 99%